Theory of Cryptography Sixth Theory of Cryptography Conference, TCC 2009, San Francisco, CA, USA, March 15-17, 2009, Proceedings - Reingold, Omer (Security and Cryptology, 2009)
This book constitutes the refereed proceedings of the Sixth Theory of Cryptography Conference, TCC 2009, held in San Francisco, CA, USA, March 15-17, 2009. The 33 revised full papers presented together with two invited talks were carefully reviewed and selected from 109 submissions. The papers are organized in 10 sessions dealing with the paradigms, approaches and techniques used to conceptualize, define and provide solutions to natural cryptographic problems.